Strategi Pemasaran Wedding Organizer ‘’House Of Imey’’ Dalam Meningkatkan Konsumen - Martha Haning Kusuma Dewi; Agung Dwi Nugroho (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The development of business in the service sector is currently growing rapidly, especially in the wedding organizer industry. The purpose of this internship is to Develop Entrepreneurial Skills by providing students with the opportunity to develop entrepreneurial skills such as global marketing, leadership, business communication, e-business, organizational culture. This applies to us, who provide wedding management and planning services. Wedding Organizer can facilitate and assist partners or couples in planning a wedding related to determining the theme, the concept of the wedding desired by the client is the core of our research. Encouraging students to think creatively and innovatively in designing and managing a business. This program can be a place for new ideas and innovative solutions to problems faced. In addition, in handling weddings, we focus on managing vendors involved in the wedding such as decoration, catering, and entertainment. Coordinating events, and ensuring that the wedding runs smoothly to increase client satisfaction and build a good reputation. A professional and qualified Wedding Organizer can improve the quality of services provided so that clients can feel satisfied and happy.